Is the Stock Market Immune to COVID-19? Evidence from Malaysian Stock Market - Kelvin Lee, Yong Ming; Pick Soon, Lee; Mohamad, Jais (Human Resource Management Academic Research Society (HRMARS), 2022)
This study aims to examine the immunity of the Malaysian sectoral indexes to the COVID-19 related news in 2020 and 2021. The findings indicated that the market volatility of the Malaysian stock market has reduced from 2020 to 2021. The results also showed that market volatility and Brent oil price movements had a significant impact on the majority of the sectors. The daily COVID-19 confirmed cases also had a greater impact than the daily COVID19 death cases towards the movements of Malaysian sectorial indexes. Investors are recommended to monitor the information related to the COVID-19 pandemic. Any dramatic changes in COVID-19 confirmed cases and death cases might cause another round of volatility in the Malaysian stock market. Risk-averse investors are recommended to pay attention to the consumer product and construction sectors. Lastly, REIT, technology, and healthcare sectors shall be another sector to be targeted after the reopening of economic activities.